The Influence of Strategic Decision Making, Business Performance, and Employee Development on Big Data Technology in HR: A Case Study of a FinTech Company in Jakarta - Tyoso, Jaluanto Sunu Punjul; Amaludin, Amaludin; Hendriana, Tengku Ine; Radnan, Yokie (Westscience Press, 2024)
This study investigates the influence of strategic decision making, business performance, and employee development on the adoption of Big Data technology in HR within a FinTech company based in Jakarta. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), data were collected through an online survey administered to employees involved in HR management. The results reveal significant positive relationships between strategic decision making, business performance, employee development, and the adoption of Big Data technology in HR. Specifically, strategic decision making and employee development are found to positively influence the adoption of Big Data technology in HR, while business performance is positively associated with both strategic decision making and employee development. These findings underscore the importance of strategic HR practices and investments in employee development for leveraging Big Data technology effectively in HR management. The study contributes to a deeper understanding of the factors driving the adoption of Big Data technology in HR and provides practical implications for HR practitioners and organizational leaders.